Small-molecule inhibition of MuRF1 prevents early disuse-induced diaphragmatic dysfunction and atrophy - Ribeiro, Fernando; Alves, Paula K. N.; Bechara, Luiz R. G.; Ferreira, Julio C. B.; Labeit, Siegfried; Moriscot, Anselmo S. (International journal of molecular sciences, 2023)
In clinical conditions such as diaphragm paralysis or mechanical ventilation, disuse-induced diaphragmatic dysfunction (DIDD) is a condition that poses a threat to life. MuRF1 is a key E3-ligase involved in regulating skeletal muscle mass, function, and metabolism, which contributes to the onset of DIDD. We investigated if the small-molecule mediated inhibition of MuRF1 activity (MyoMed-205) protects against early DIDD after 12 h of unilateral diaphragm denervation. Wistar rats were used in this study to determine the compound’s acute toxicity and optimal dosage. For potential DIDD treatment efficacy, diaphragm contractile function and fiber cross-sectional area (CSA) were evaluated. Western blotting investigated potential mechanisms underlying MyoMed-205’s effects in early DIDD. Our results indicate 50 mg/kg bw MyoMed-205 as a suitable dosage to prevent early diaphragmatic contractile dysfunction and atrophy following 12 h of denervation without detectable signs of acute toxicity. Mechanistically, treatment did not affect disuse-induced oxidative stress (4-HNE) increase, whereas phosphorylation of (ser632) HDAC4 was normalized. MyoMed-205 also mitigated FoxO1 activation, inhibited MuRF2, and increased phospho (ser473) Akt protein levels. These findings may suggest that MuRF1 activity significantly contributes to early DIDD pathophysiology. Novel strategies targeting MuRF1 (e.g., MyoMed-205) have potential therapeutic applications for treating early DIDD.
Gesehen am 29.08.2024